A cyanine-derivative photosensitizer with enhanced photostability for mitochondria-targeted photodynamic therapy. Issue 90 (24th October 2019) - Zhao, Xuan; Yang, Yanjun; Yu, Yan; Guo, Siming; Wang, Wenxing; Zhu, Sumin
Abstract : A cyanine-derivative photosensitizer was synthesized with excellent photostability for photodynamic therapy via targeting the cancer cell mitochondria. Abstract : A cyanine-derivative photosensitizer, CYBF2, was synthesized for photodynamic therapy of cancer. The photosensitizer can be activated by red-light with enhanced photostability compared to traditional cyanine photosensitizers. CYBF2 was able to generate singlet oxygen inside the cell mitochondria, which efficiently resulted in apoptosis of cancer cells.